The Role of Photobionts as Drivers of Diversification in an Island Radiation of Lichen-Forming Fungi - Blázquez, Miguel; Hernández-Moreno, Lucía S.; Gasulla, Francisco; Pérez-Vargas, Israel; Pérez-Ortega, Sergio (Frontiers in Microbiology, 2022)
Speciation in oceanic islands has attracted the interest of scientists since the 19th century. One of the most striking evolutionary phenomena that can be studied in islands is adaptive radiation, i. e., when a lineage gives rise to different species by means of ecological speciation. Some of the best known examples of adaptive radiation are charismatic organisms like the Darwin finches of the Galapagos and the cichlid fishes of the great African lakes. In these and many other examples a segregation of the trophic niche has been shown to be an important diversification driver. Radiations are known in other groups of organisms such as lichen-forming fungi. However, very few studies have investigated their adaptive nature, and none have focused on the trophic niche. In this study we explore the role of the trophic niche in a putative radiation of endemic species from the Macaronesian Region, the Ramalina decipiens group. The photobiont diversity was studied by Illumina MiSeq sequencing of the ITS2 region of 197 specimens spanning the phylogenetic breadth and geographic range of the group. A total of 66 amplicon sequence variants belonging to the four main clades of the algal genus Trebouxia were found. Approximately half of the examined thalli showed algal coexistence, but in most of them a single main photobiont amounted to more than 90% of the reads. However, there were no significant differences in photobiont identity and in the abundance of ITS2 reads across the species of the group. We conclude that a segregation of the trophic niche has not occurred in the R. decipiens radiation.